Molecular dynamics study of ACBP denaturation in alkyl sulfates demonstrates possible pathways of unfolding through fused surfactant clusters. Issue 4 (2nd December 2019) - Poghosyan, Armen H; Schafer, Nicholas P; Lyngsø, Jeppe; Shahinyan, Aram A; Pedersen, Jan Skov; Otzen, Daniel E
Abstract: Anionic surfactants denature proteins at low millimolar concentrations, yet little is known about the underlying molecular mechanisms. Here, we undertake 1-μs-long atomistic molecular dynamics simulations of the denaturation of acyl coenzyme A binding protein (ACBP) and compare our results with previously published and new experimental data. Since increasing surfactant chain length is known to lead to more rapid denaturation, we studied denaturation using both the medium-length alkyl chain surfactant sodium dodecyl sulfate (SDS) and the long alkyl chain surfactant sodium hexadecyl sulfate (SHS). In silico denaturation on the microsecond timescale was not achieved using preformed surfactant micelles but required ACBP to be exposed to monomeric surfactant molecules. Micellar self-assembly occurred together with protein denaturation. To validate our analyses, we calculated small-angle X-ray scattering spectra of snapshots from the simulations. These agreed well with experimental equilibrium spectra recorded on ACBP-SDS mixtures with similar compositions. Protein denaturation occurs through the binding of partial micelles to multiple preferred binding sites followed by the accretion of surfactant monomers until these partial micelles merge to form a mature micelle and the protein chain is left disordered on the surface of the micelle. While the two surfactants attack in a similar fashion, SHS's longer alkyl chain leads to a more efficient denaturation through the formation of larger clusters that attack ACBP, a more rapid drop in native contacts, a greater expansion in size, as well as a more thorough rearrangement of hydrogen bonds and disruption of helices.